Rājādhirāt: From the History to an Influential literature for Mon-accented Thai traditional Repertoires - Jarun Kanchanapradit; Wanida Bhrammaputra (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
This article aimed to study Mon-accented Thai traditional repertoires through Rājādhirāt literature, which owe its origin from the Chronicles of the Mon. It is the story about the battle between the king Rājādhirāt of Pegu and King Farang Mang Kong of Ava. The translated Thai language prose version was arranged by Chao Phraya Phra Khlang (Hon), a poet master during King Rama I. Later during King Rama V, the Rājādhirāt was adapted for theatrical play – Lakorn Pan Tang – leading to development in musical front in order to assign appropriate Mon-accented musical pieces for the characters, their expressions, and story. Anthropologically, Rājādhirāt Literature was not only an entertainment, but also a revival of Mon-accented Thai traditional repertoires which have been associated with the Thai society for so long. The repertoires served as a reminder of once-flourishing Mon history through literature, play, music. Analysis of historical evidence, concerned persons such as the translator of Rājādhirāt from Burmese to Thai language, experienced Thai musician who played and assigned the repertoires; and expressive interpretation of musical repertoires from Rājādhirāt play by the Fine Arts Department are the integral process that made this article present another perspectives of Mon-accented Thai traditional repertoires while featuring relationship between literature, play and music in Thailand.